Online distance learning readiness among students: a comparative study between mathematics and statistics courses / Bushra Abdul Halim ... [et al.] - Abdul Halim, Bushra; Zainudin, Siti Nursyahira; Fuzi, Siti Fairus; Jama, Siti Ramizah; Zahidi, Nurul Emyza; Jusoh @ Hussain, Nordianah; Wan Hassan, Wan Hartini (Universiti Teknologi MARA, Perlis, 2022)
In early January 2020, the whole world, including Malaysia, was threatened by the coronavirus (COVID-19) pandemic. Malaysia implemented phases of Movement Control Orders (MCO) to halt the spread of the COVID-19 pandemic. As a result, educational institutions have been impacted, as face-to-face learning on campus has been replaced by remote Online Distance Learning (ODL) at home for all courses offered. The purpose of this study is to determine whether there is a significant difference in students' ODL readiness dimensions for mathematics/statistics courses, as well as the effect of students' ODL readiness dimensions on mathematics/statistics performance. This research referred to five dimensions from the Online Learning Readiness Scale (OLRS); computer/Internet self-efficacy, self-directed learning, learner control, motivation for learning, and online communication self-efficacy to measure students' ODL readiness. Data were collected from 511 students enrolled in online mathematics/statistics courses at Universiti Teknologi MARA Melaka during the academic session March - July 2020. The one-way repeated analysis of variance, one-way multivariate analysis of variance (one-way MANOVA), and multiple regression analyses were used as statistical analyses in this study. The findings indicated that students enrolled in statistics courses showed higher readiness scores in computer/Internet self-efficacy and self-directed learning than students taking mathematics courses. Additionally, the results indicate that self-directed learning in ODL affected students' mathematics/statistics performance. In conclusion, students taking statistics courses were more prepared and performed better in learning through ODL than students taking mathematics courses.